Desain Model Monate: Movie Analysis and Debate untuk Pembelajaran Literasi Sosial - Utami, Fariza Wahyu; Wardani, Li’anatus Sukma; Segara, Nuansa Bayu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Literacy skills in the 21st century for the cognitive development of any student are vital. Various literacy skills are a derivative of 21st-century skills. Social literacy is one of the goals of the social studies learning process. It is also necessary to improving supporting abilities such as the ability to communicate, collaborate and think critically for each student. They can mount their competencies through learning experiences from the surrounding environment. One of the innovations is for improving students' social literacy skills in social studies learning is using the